Company Size Moderated Audit Delay Determination on LQ45 Companies on the Indonesia Stock Exchange - Ayunita Ajengtiyas Saputri Mashuri; Husnah Nur Laela Ermaya (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to observe the effect of Auditor switching, profitability, solvency, auditor quality on audit delay and firm size in its ability to moderate the effect of auditor switching, profitability, solvency and auditor quality on audit delay in LQ 45 companies listed on the IDX in the 2016-2018 period as research samples. This research is a quantitative research with multiple linear regression analysis technique and a special application of multiple linear, namely Moderated Regression Analysis (MRA) to measure the moderating variable. The research results obtained are simultaneously the profitability and moderating variables of firm size have an impact on audit delay. Meanwhile, based on the partial test, it shows that (1) Auditor switching has no a significant effect on audit delay (2) Profitability has a significant effect on audit delay, (3) Solvency has no a significant effect on audit delay, (4) Auditor Quality has no a significant effect on audit delay (5) Company size is not able to moderate the effect of Auditor switching on audit delay (6)Company size is able to moderate the effect of profitability on audit delay, (7) Company size is not able to moderate the effect of solvency. against audit delays (8) Company size is not able to moderate the effect of auditor quality against audit delays